Diagnosis and treatment of nervous system diseases at the beginning of the 19th century in Vilnius university clinics - E. Sakalauskaitė-Juodeikienė; G. Motiejūnas; D. Jatužis (Neurologijos seminarai)
Practical skills have been and are still important in productive professions such as metal and glass processing, watch and tool manufacturing, building, ship building and others. A physician must also acquire certain practical skills in order to properly diagnose the disease and to treat the patient. In this article we overview the origins of medical students’ training (“at the bedside of the sick”), describe the birth of the Vilnius university clinics, present the statistical data of the treated patients, and analyse diagnoses and treatment methods of nervous system diseases at the beginning of the 19th century in Vilnius. Anthropometric, morphometric, somatic, and neurological examinations were performed in Vilnius clinics. Vilnius physicians and professors of clinical medicine, as well as medical students evaluated pupillary light reflex, patient’s response to painful stimuli, their mental condition, paroxysmal movements, limb position, weakness of limb movements, some sensory modalities – touch, vision, audition, smell, taste, as well as dysfunction of pelvic organs, among the other signs and symptoms. In Vilnius, as in other European clinics, the causes of the diseases were sought in the internal organs (the influence of the solidism theory), but autopsy findings usually revealed the brain and spinal cord congestion with blood, confirming the inflammation of the nervous system (or humoralism) theory. The level of diagnostics and treatment of nervous system diseases in Vilnius corresponded to the level of Western Europe in the first half of the 19th century.